The role of subsidy in ensuring the sustainability of small-scale anaerobic digesters in Odisha, India. (October 2016) - York, L.; Heffernan, C.; Rymer, C.
Abstract: Small-scale anaerobic digester installation has been a development objective of the Indian government to provide rural households clean fuel. Anaerobic digester installation is heavily subsidised. Depending on caste, the rate of subsidy offered for the smallest system available (1 m 3 ) varies between 32.35% and 41.18% of the total installation price. Yet, there are gaps in knowledge regarding the usefulness of such subsidies from a sustainability perspective. A cost-benefit analysis was conducted to evaluate the circumstances required for digester sustainability. The analysis used household data collected from 115 cattle owning households in Odisha, India to evaluate profitability at three levels of subsidy (none, General caste subsidy, and Schedule Caste/Schedule Tribe subsidy). Additional analyses considered the effect of; taking a loan, replacing electric lighting with biogas lighting, and the wealth level of the household. The results indicated that access to subsidy improved profitability. Yet, profitability could be achieved without the use of subsidy. The level of benefit accrued by households was similar independent of wealth. However, the provision of subsidy was essential for ensuring profitability for those households required to take a loan to meet the expense of installation. Such findings highlight the importance of subsidy as a means of including the poor. Highlights: Subsidy is not required to achieve anaerobic digester profitability. Profitability can be improved by replacing electric lighting with biogas lamps. Loan repayments without subsidy make anaerobic digesters unprofitable. Packaging subsidy alongside loans will better target those most in need of support. The technology is sustainable unless households cannot meet installation costs.